Axially loaded built-up C-section cold-formed steel with holes - Muhammad Izzuddin, Harisfadzill (2018)
An experimental investigation was conducted to study the behavior of built-up cold-formed steel. The built-up studs in this study consisted of two C-sections oriented back-to-back forming an I-shaped cross-section. The dimension for diameter built-up specimens are divided into two that are 103mm and 203mm to be investigated. For each specimen, the studs were connected to each other with two self-drilling screws spaced at a set interval. A cold-formed steel track section was connected running perpendicular to each end of the built-up stud with a single self-drilling screw through each flange of the C-sections. The purpose of the track section was to keep the ends of the studs together and represents a common end attachment. The specimens are welded with the specific size of steel plate before being testing. The purpose of welded specimen are to hold the specimens during testing and for more accurate result obtain. The result of the specimen can be obtained by the ultimate load from each specimen and to study the buckling behavior due to the different opening position in specimens.